Formación docente para la inclusión educativa de estudiantes con dislexia - Bustamante Alvarado, Noemí Chanena (2021)
This research work analyzes learning difficulties, in particular dyslexia, which is identify as an impediment in the reading and writing process that affects children and adolescents with normal or superior sensory and intellectual problems. The preparation of the teacher in their training for educational inclusion is intend to help children with this type of disorder in the first grades of primary school to learn to acquire reading and writing skills, which are general found at the beginning of literacy. The methodology used was of a mixed approach, taking bibliographic information on the subject and a field investigation. Questionnaires with closed questions were use that were applies to the survey and for the interview, open questions in order to obtain data that would allow the construction of a profile of the interviewees. The quantitative analysis was complement with the elaboration of statistical tables and graphs. The results showed that the majority of teachers construct a negative view of dyslexia due to ignorance and this implies unfavorable positions and practices for the inclusion of these students..........